HUBUNGAN KADAR GLUKOSA DARAH DENGAN BETA HIDROKSI BUTIRAT PADA PENDERITA DIABETES MELITUS - Mardiana Mardiana Mardiana; Warida Warida Warida; Siti Rismini Rismini (Jurnal Ilmu dan Teknologi Kesehatan, 2014)
Diabetes Mellitus (DM) is a metabolic syndrome caused by deficiency or decreasing of insulin effectiveness that affect metabolism of carbohydrate, protein and fat. This syndrome gives high mortality and morbidity brought about by diabetic ketoacidosis complications as a result of the increasing of fat metabolism. Ketone body in this research means beta hydroxybutyrate (beta-OH butyrate). This research that utilized 778 analysis data of beta-OH butyrate in blood resulted in 449 data (57.71 %) in a normal range (<0.6 mmol/L), while 329 data (42.29 %) in an abnormal range (> 0.6 mmol/L). From statistics test found p value 0,000 with 5 % (0.05 ), that means there is a relation between blood glucose level and beta-OH butyrate level. The Pearson correlation of 0,286 or weak correlation, it means that increasing of blood glucose level is not always followed by increasing of beta-OH butyrate level.